The Regulation of the Digital Transition in the EU: Opportunities & Challenges in the EU’s Fight Against Disinformation - de Vries, Sybe Alexander (South East Asian Journal of Advanced Law and Governance (SEAJ-ALGov), 2025)
Digital technologies allow for the spread and dissemination of hate speech and disinformation at previously unseen scale and speed, which threaten citizens’ right to (accurate) information and human dignity, and the core values of the rule of law and democracy, which are for the European Union enshrined in Article 2 TEU. According to the European Commission, disinformation constitutes “false or misleading content that is spread with an intention to deceive or secure economic or political gain, and which may cause public harm”. The recently adopted EU’s Digital Services Act (DSA) seeks to combat harmful content online and disinformation, although disinformation is only referred to and not defined in its recitals. In this paper it will be assessed to what extent the DSA within the context of Europe’s Digital Single Market is fit for purpose to address the challenges of dissemination.